Developing land-use agreements in commodity cash crop production that meet the needs of landowners and smallholders - Koczberski, Gina; Curry, George; Rogers, D.; Germis, E.; Koia, M. (Australian Centre For International Agriculture Research (ACIAR), 2013)
This paper reports on the research to design a Clan Land Usage Agreement (CLUA) for oil palm smallholders planting oil palm on the customary land belonging to others in West New Britain province and Northern Province. These oil palm holdings are known in the industry as customary rights purchase (CRP) blocks and they make up approximately 15% of the total area of smallholder oil palm in West New Britain. The CLUA was designed to deal with the increasing number of land disputes on CRP blocks. To develop the CLUA, lengthy in-depth interviews and meetings were held with smallholders and landowners to document: the types of land transactions on CRP blocks; how tenure and access rights were acquired by migrants; and the underlying causes of the land disputes on CRP blocks. This information formed the basis of a CLUA template that was acceptable to landowners, migrant smallholders and the broader industry. The completed CLUA template provides more secure land tenure for CRP growers and ensures that all members of the landowning group with customary rights to the land where these CRP blocks are located consent to the land transactions with migrants. By designing the CLUA in partnership with landowners, migrant farmers and other industry stakeholders, the likelihood of the CLUA being accepted was significantly improved.